If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y * 3y = 0 Reorder the terms for easier multiplication: 7 * 3y * y = 0 Multiply 7 * 3 21y * y = 0 Multiply y * y 21y2 = 0 Solving 21y2 = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '21'. y2 = 0 Simplifying y2 = 0 Take the square root of each side: y = {0}
| 7m+4n-3m+7n= | | x/-19=-2 | | (7x+2)-(2x^2+6x+8)= | | 4*5=585 | | 2*3=290 | | (3x^2-7x+2)+(4x^2+5x+5)= | | 28-4x=156 | | 3j-(j-4)+3= | | y=arcsin(x+2) | | -12x=-70 | | 4x-7=3.8 | | 5x+4x=70 | | 6(x-3)-4x=32 | | 4(-3.4)+1/3=(-3.4)-5/2 | | 0.03x-0.4x=2.85 | | a+0.8=-0.8a+3.86 | | 28+4x=156 | | -10=8x-3 | | 4(x+2)-6x+4=-42 | | 2+x=58 | | (-a^2+2)-(a^2-4)+(6a^2-5a*3)= | | 5x+140= | | .7=.35 | | 4s-12=5s+15 | | (4x^2+9x-2)+(4x^2+4x+19)-(8x^2-14)= | | 3(2x-1)=3x+1/2 | | 8K+1-1=17 | | 3(12-x)+6x=10 | | x+4=5x-20 | | 96=3(4x-8) | | 5(m-4)+6m=5(m+3)-7 | | -10x^2+6x+3=0 |